Analisis Pengaruh Suku Bunga Kredit dan Kurs Terhadap Ekspor Nonmigas Provinsi Riau - Sulaiman '; Rahmat Richard; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted by analyzing data of non-oil exports of Riau Province, the data rate and the data rate loan. This study aims to determine how the effect of mortgage interest rates and the exchange rate against the value of non-oil exports Riau Province 2001-2013 period. The data used are secondary data are time series for 13 years, and method of data analysis used in this study is the Ordinary Last Square (OLS) multiple linear regression model to calculate the tool eviews program. From the calculation results were obtained coefficient value of each independent variable is X1 (lending rates) amounted to 16772.92 means that if there is an increase in lending rates by 1%, the value of non-oil exports Riau province decreased by USD 16,772,920. Furthermore, the value of coefficient X2 (exchange) is 785,797.6 means that if there is an increase of USD 1.00 dollar exchange rate, the value of non-oil exports Riau Province increased by USD 785 797 600. In this study also tested the level of a significant level of 95% (α = 0.05), the calculation of the results obtained probabiliti for lending rates by 0.0002, and the exchange rate of 0.4719. It can be seen that lending rates have a significant effect in influencing the value of non-oil exports Riau province, because probabiliti for interest rates is smaller than α = 0.05, while the exchange rate has no significant effect on the value of non-oil exports Riau Province is characterized by probabiliti case for more rate greater than α = 0.05. changes in non-oil exports Riau able to simultaneously explained by the variables in lending rates (X1) and exchange rate (X2) is 77.39 percent, while the remaining 22.61 per cent is explained by other factors that are not included in the model used in this research.Keywords: Investment Interest Rate, Exchange Rate, Non-oil Exports Riau Province